The Impact of Gas Production Decline to LPG Recovery and Optimization Strategy to Prevent LPG Facility From Shutdown - Ameria Eviany, Sutrasno Kartohardjono (International Journal of Advanced Science and Technology, 2020)
The decrease in gas from the production well is caused by two main factors, namely the decline in formation productivity and the decrease in the production rate. The impact of the steep decline in production has resulted some risks in some operating equipment in both offshore and onshore production facilities being over capacity, not optimum in operation, and total shutdown in the LPG facility. To prevent this occurrence, alternatives are needed to maintain the rate of decline in production, both from the well side and from the equipment in the facility. Handling the production problems with right actions will return the producing wells with optimum capacity. In terms of equipment, for dynamic equipment such as rotating equipment, the equipment has a specific range of parameters or operating limits, thus modifications are required. Resizing the rotating equipment including the control system has been assessed and selected to be the most effective and efficient method to prevent the cessation of LPG plant in producing LPG. The direct impact of restaging the rotating equipment extends the lifetime of LPG plant and also gain some incremental of LPG recovery.